The development of energy efficient vehicle using Natural Gas Technology (NGV) - Muhammad Alif Hafizi, Jasmani (2018)
Natural Gas Vehicle (NGV) is an alternative fuel vehicle for autonomous mobility that uses Compressed Natural Gas (CNG) or Liquefied Natural Gas (LNG). NGV is different to the vehicles which are using propane (LPG). Both fuels are different in composition. Basically, the natural gas is a mixture of gases which are rich in hydrocarbons. Methane, nitrogen, carbon dioxide and etc. are naturally found in the atmosphere. Furthermore, natural gas is mainly used as fuel for generating electricity and heat. It is clearly can substitute petrol for the engine’s combustion to supply the power. Besides, natural gas also has a cleaner gas emission compared to the petrol. The emission of the hazardous gas such as carbon monoxide, nitrogen oxide, and others are higher emitted from the combustion of the petrol compared to the combustion of the natural gas. The purpose of this project is to install the NGV system on the Proton Waja 1.6 (A) CamPro. Other than that, this project also one of the steps for UMP to develop our university to become environmentally friendly as to support the UMP Green program. Besides, it is also for the significant purpose as to utilize the one and only NGV station in Kuantan which is located near to our campus in Gambang. After the successful NGV installation, the performance for the Proton Waja is tested. The result shows that the performance for the car is same as it is using petrol for the fuel combustion. Next, for the fuel consumption, there is about 50% of saving when the NGV is used compared to the petrol usage. This is proven that using NGV for the car can reduce the cost of the transportation without any lack of performance.